Transforming Organizational Culture in Islamic Educational Institutions: Cultivating a Quality-Oriented Learning Environment for Academic Excellence - Yakin, Ainul; Hefniy; Abu Hasan Agus; Hasan Baharun; Akmal Mundiri (Journal of Educational Management Research, 2025)
This study explores the transformation of organizational culture in Islamic educational institutions, with a specific focus on developing a quality-oriented learning environment aimed at enhancing both academic performance and character formation. Employing a qualitative approach through an ethnographic case study design, the research was conducted between 2024 and 2025. Data were collected through in-depth interviews with eight key informants, six months of participatory observation, and analysis of institutional documents. Findings reveal that a tauhid-based cultural transformation successfully fostered a high-quality learning ecosystem through the synergy of three fundamental dimensions: the internalization of spiritual values as a foundation for strategic decision-making, transformational leadership that cultivates a shared vision and empowers stakeholders, and the integration of constructivist pedagogy through project- and inquiry-based learning models. Character development outcomes were equally notable, reflected in reduced disciplinary violations, improved consistency in religious practices, and heightened social empathy among students. This study contributes theoretically by introducing the concept of a Tauhid-Based Quality Learning Environment (TQLE)—a holistic framework that harmonizes academic excellence with Islamic character formation. Practically, it offers an implementable model for Islamic educational institutions seeking to embed spiritual values into sustainable quality education practices.